Low levels of knowledge, attitudes and preventive practices on leptospirosis among a rural community in Hulu Langat district, Selangor, Malaysia - Nozmi, Noramira; Samsudin, Suhailah; Sukeri, Surianti; Shafei, Mohd Nazri; Wan Mohd, Wan Mohd Zahiruddin; Arifin, Wan Nor; Idris, Norazlin; Saudi, Siti Nor Sakinah; Abdullah, Nurul Munirah; Abdul Wahab, Zainudin; Tengku Jamaluddin, Tengku Zetty Maztura; Abd Rahman, Hejar; et al. (Multidisciplinary Digital Publishing Institute, 2018)
Little is known on the knowledge, attitudes and preventive practices (KAP) of leptospirosis worldwide. This study embarked on assessing the KAP of leptospirosis among rural communities in Malaysia. A total of 444 participants (223 male; 221 female) aged between 18 and 81 years old were surveyed by using a self-administered questionnaire. A majority of participants had poor knowledge level (57.0%), unacceptable attitudes (90.3%) and unacceptable preventive practices (69.1%) on leptospirosis, and only 29.7% knew "rat-urine disease" as leptospirosis. Only 34.2% of the participants knew the bacteria could enter via wound lesions. Ethnicity and income were strongly associated with knowledge level and preventive practices, respectively (p-values < 0.05). As for attitudes, ethnicity, income and education type were significantly associated (p-values < 0.05). Only 36.5% of the participants were willing to see a doctor and did not mind if their house or surrounding area is dirty (59.7%). Surprisingly, only 32.9% had used rubber boots during floods. By logistic regression analysis, ethnicity was the only significant predictor for both knowledge level (an odds ratio (AOR) = 0.39, 95% confidence interval (CI) = 0.222-0.680) and preventive practices (AOR = 1.81, 95% CI = 1.204-2.734). Ethnicity (AOR = 0.40, 95% CI = 0.239-0.665), income (AOR = 1.58, 95% CI = 1.041-2.385) and education type (AOR = 3.69, 95% CI = 1.237-10.986) were strong predictors for attitudes. Among the KAP variables, attitude (AOR = 4.357, 95% CI = 2.613-7.264) was the only predictor for the preventive practices by logistic regression analysis. The KAP elements on leptospirosis are still lacking and poor health seeking behavior and attitudes are of our utmost concern. Thus, effective strategies should be planned to impart knowledge, and develop proactive approaches and good preventive modules on leptospirosis to this leptospirosis-prone community.